2023
DOI: 10.1017/pds.2023.101
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Collaborative Cad Modelling Patterns of High-Performing and Low-Performing Teams

Abstract: The development of cloud-based Computer-aided design (CAD) enabled real-time CAD collaboration between multiple designers. While this technology has great potential to change the way CAD work is done, it is still little explored. This paper presents a case with two high-performing and two low-performing three-member teams monitored with non-invasive methods (log data) during a six-week design project. The results show that high-performing teams focused more on the editing of assembly, while low-performing team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 13 publications
(21 reference statements)
1
7
1
Order By: Relevance
“…Furthermore, in terms of CAD actions concerning the action type within the design sprint format, the study found a series of insights that both corroborate and diverge from the existing literature on collaborative CAD usage. Predominantly, a tendency among three out of four observed teams to prioritize the Creating over Editing actions, aligning with Deng et al (2022) data, but diverges from Celjak et al (2023), who suggests that Editing is the most frequent CAD action. This implies that teams predominantly concentrated on generating new features or experimenting with their different aspects, possibly without revising them, taking a more iterative approach for enhanced design.…”
Section: Team-wise Cad Usagementioning
confidence: 89%
See 4 more Smart Citations
“…Furthermore, in terms of CAD actions concerning the action type within the design sprint format, the study found a series of insights that both corroborate and diverge from the existing literature on collaborative CAD usage. Predominantly, a tendency among three out of four observed teams to prioritize the Creating over Editing actions, aligning with Deng et al (2022) data, but diverges from Celjak et al (2023), who suggests that Editing is the most frequent CAD action. This implies that teams predominantly concentrated on generating new features or experimenting with their different aspects, possibly without revising them, taking a more iterative approach for enhanced design.…”
Section: Team-wise Cad Usagementioning
confidence: 89%
“…The study's objective was to explore CAD usage patterns in design sprint format among four internationally dislocated student teams. It focuses on collaborative CAD usage during online design sprint, comparing team-wise CAD usage through a structured review of relevant literature fosuced on conventional collaborative CAD usage during PBL (Celjak et al, 2023) or case study (Deng et al, 2022) and a two-day analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations